Evaluation of the limit state and cyclic life of structural materials under thermal fatigue - Gopkalo, A.P. (Проблемы прочности, 2009)
The relationship between the cyclic life and reduced stress in half-cycles of heating (compression) has been established, as well as the parameters defining the transition from the quasi-static to fatigue fracture mode and their threshold values. An approach has been proposed for the evaluation of cyclic life under thermal fatigue, which involves a preliminary prediction of the fracture mode and the use of calculation relationships corresponding to the predicted mode of fracture. Установлена зависимость циклической долго вечности от уровня приведенных напряжений в полуциклах нагрева/охлаждения, а также параметры, определяющие переход от квазистатического к усталостному разрушению и соответствующие им пороговые значения. Предложен новый подход к оценке циклической долговечности при термоусталости, который включает в себя предварительный прогноз типа разрушения и использование расчетных зависимостей, соответствующих прогнозируемому типу разрушения.